Sur une th´eorie des m´econnaissances en calcul des structures - Ladev eze, Pierre; Puel, Guillaume; Deraemaeker, Arnaud; Romeuf, Thierry (European Journal of Computational Mechanics, 2004)
The quantication of the quality of a structural mechanical model remains a major issue today, with the use of an increasing number of methods in order to validate a model in comparison with an experimental reference. This paper presents a new theory based on the concept of Lack of Knowledge combining convex uncertainty models with probabilistic features by introducing for each substructure two bounds of the strain energy as stochastic variables. A general strategy of reduction of the lack of knowledge is discussed and applied to academic as well as industrial cases.